Penguatan Resilensi Perempuan Melalui Modal Sosial di Era Adaptasi Kebiasaan Baru Pandemi Covid-19 - Malihah, Elly; Komariah, Siti; Wilodati, Wilodati; Munggaran, Rengga Akbar; Utami, Lingga; Rizkia, Arindini; Ahmad, Yazied Taqiyuddin (Martabat: Jurnal Perempuan dan Anak, 2021)
Abstract: The increasing issue of gender responsiveness to women's burdens as a result of COVID-19 has become the background for the implementation of women-based community empowerment under the name "Patali Gumbira". The implementation of women's empowerment "Patali Gumbira" has become one of the issues to prepare women in adapting to the new habits of COVID-19. To build women's resilience based on social capital, their knowledge, experience, and aspirations in responding to the impact of COVID-19. In this study, the Feminist Participatory Action Research (FPAR) approach was used, which made women the center for critical, independent, and creative thinking. The findings in this study indicate that the empowerment of "Patali Gumbira" is a form of means of women's social resilience through a structured framework of education, advocacy, and economic systems utilizing social networks, one of which is strengthening the organization of PKK women in the village public sphere. This strengthening effort is driven by the inclusion of various training including 1) strengthening women's motivation in facing adaptation to new habits due to COVID-19; 2) strengthening women's leadership in an effort to build their potential capabilities; 3) advocacy in the prevention and handling of cases of violence against women, and 4) hairdressing soft skills training as an opportunity for women's business services on an ongoing basis. Efforts to overcome social impacts during the COVID-19 pandemic are strengthening women's resilience and becoming confident in building a sense of belonging. Keywords: Covid 19, Social Capital, Social Resilience, Women Empowerment Abstrak: Meningkatnya isu responsif gender terhadap beban perempuan sebagai dampak COVID-19, menjadi latar belakang terselenggaranya pemberdayaan masyarakat berbasis perempuan dengan nama “Patali Gumbira”. Pelaksanaan pemberdayaan perempuan “Patali Gumbira” ini menjadi salah satu isu mempersiapkan perempuan dalam adaptasi kebiasaan baru COVID-19. Dalam upaya membangun resiliensi perempuan tersebut berdasarkan modal sosial pengetahuan, pengalaman, dan aspirasi mereka dalam menyikapi dampak COVID-19. Pada penelitian ini digunakan pendekatan Feminist Participatory Action Research (FPAR), yang menjadikan perempuan sebagai sentral untuk befikir kritis, mandiri serta kreatif. Temuan dalam kajian ini menunjukkan bahwa, pemberdayaan “Patali Gumbira” menjadi bentuk sarana resiliensi sosial Perempuan melalui kerangka sistem edukasi, advokasi dan ekonomi yang terstruktur memanfaatkan jejaring sosial salah satuanya penguatan organisasi Ibu-ibu PKK di ranah publik desa. Upaya penguatan ini didorong dengan termuatnya berbagai pelatihan diantaranya: 1) penguatan motivasi perempuan dalam menghadapi adaptasi kebiasaan baru akibat COVID-19; 2) penguatan kepemimpinan perempuan dalam upaya membangun kemampuan potensinya; 3) advokasi dalam pencegahan dan penanganan kasus kekerasan terhadap perempuan, dan 4) pelatihan softskill tata rambut sebagai peluang jasa usaha perempuan secara berkelanjutan. Upaya mengatasi dampak sosial di masa pandemi COVID-19 menjadi penguatan resiliensi para perempuan dan menjadi keyakinan dalam membangun rasa memiliki. Kata kunci: Covid 19, Modal Sosial, Pemberdayaan Perempuan, Resiliensi sosial